Tile-based 360-degree video streaming for mobile virtual reality in cyber physical system. (November 2018) - Son, Jangwoo; Ryu, Eun-Seok
Abstract: Today, the demand for and interest in virtual reality (VR) is increasing, since we can now easily experience VR in many applications. However, the computational ability of mobile VR is limited compared to that of tethered VR. Since VR represents a 360-degree area, providing high quality only for the area viewed by the user saves considerable bandwidth. Therefore, we propose a new tile-based streaming method that transforms 360-degree videos into mobile VR using high efficiency video coding (HEVC) and the scalability extension of HEVC (SHVC). While the SHVC base layer (BL) represents the entire picture, the enhancement layer (EL) can transmit only the desired tiles by applying the proposed method. By transmitting the BL and EL using region of interest (ROI) tiles, the proposed method helps reduce not only the computational complexity on the decoder side but also the network bandwidth.